2013
DOI: 10.1534/genetics.113.153973
|View full text |Cite
|
Sign up to set email alerts
|

Population Growth Inflates the Per-Individual Number of Deleterious Mutations and Reduces Their Mean Effect

Abstract: This study addresses the question of how purifying selection operates during recent rapid population growth such as has been experienced by human populations. This is not a straightforward problem because the human population is not at equilibrium: population genetics predicts that, on the one hand, the efficacy of natural selection increases as population size increases, eliminating ever more weakly deleterious variants; on the other hand, a larger number of deleterious mutations will be introduced into the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
72
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 51 publications
8
72
1
5
Order By: Relevance
“…It has also been shown that genetic architecture (Gazave et al 2013;Simons et al 2014), the performance of single-marker tests of association (Lohmueller 2014a,b), and selection scans (Teshima et al 2006) are also sensitive to nonequilibrium evolutionary forces. However, these studies have focused on stepwise population growth (rather than state-of-the-art models of explosive growth) (Lohmueller 2014a,b), investigated simplified selection models (rather than models inferred from human polymorphism data) (Simons et al 2014), or have only indirectly considered the impact on complex traits (Gazave et al 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that genetic architecture (Gazave et al 2013;Simons et al 2014), the performance of single-marker tests of association (Lohmueller 2014a,b), and selection scans (Teshima et al 2006) are also sensitive to nonequilibrium evolutionary forces. However, these studies have focused on stepwise population growth (rather than state-of-the-art models of explosive growth) (Lohmueller 2014a,b), investigated simplified selection models (rather than models inferred from human polymorphism data) (Simons et al 2014), or have only indirectly considered the impact on complex traits (Gazave et al 2013).…”
mentioning
confidence: 99%
“…It has also been shown that genetic architecture (Gazave et al 2013;Simons et al 2014), the performance of single-marker tests of association (Lohmueller 2014a,b), and selection scans (Teshima et al 2006) are also sensitive to nonequilibrium evolutionary forces. However, these studies have focused on stepwise population growth (rather than state-of-the-art models of explosive growth) (Lohmueller 2014a,b), investigated simplified selection models (rather than models inferred from human polymorphism data) (Simons et al 2014), or have only indirectly considered the impact on complex traits (Gazave et al 2013). Some debate over the parameterization of complex trait models has resulted in a range of conclusions about the impact of evolutionary events on trait variance and the relative importance of rare alleles to complex traits (Lohmueller 2014b;Simons et al 2014); and although recent work has argued that demographic events have had little effect on deleterious load in humans (Simons et al 2014;Do et al 2015), it is less clear how demography affects the genetic variance of traits under selection.…”
mentioning
confidence: 99%
“…While changes in population size do affect the relationship between effect size and mutation frequency [48][49][50][51][52][53][54][55][56][57][58][59][60][61] (Fig 1 and S5 Fig), different mappings of genotype to trait value do this in radically different ways for the same demographic history (Fig 1). From an empirical perspective, our findings suggest that re-sequencing in large samples is likely the best way forward in the face of the allelic heterogeneity imposed by the presence of rare alleles of large effect.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the number of rare alleles due to population growth is a well established theoretical and empirical result [48][49][50][51][52][53][54][55][56][57][58][59][60][61]. The exact relationship between rare alleles [4,17,26,62,63], and the demographic and/or selective scenarios from which they arose [21,22,64], and the genetic architecture of common complex diseases in humans is an active area of research.…”
Section: Additive and Dominance Genetic Variance In The Populationmentioning
confidence: 99%
See 1 more Smart Citation